Preventive Mechanism, Therapeutic Property,Pharmacokinetics And Benefitsof Asiatic Acid - A Triterpenoid Of Centella Asiatica In Alzheimer Disease: An In-Depth Review - Chakraborty, Sudipta; Sinha, Abhipsa (Asian Journal of Pharmaceutical Research and Development, 2023)
Alzheimer's disease (AD) remains the most prevalent form of age-related dementia worldwide, and it has no cure. Memory loss, difficulty communicating, depression, agitation, mood swings, and psychosis all develop gradually in this disorder. Reduced physical activity, infection, smoking, and the prevalence of diseases like obesity and diabetes all pose a risk for the development of AD. Current synthetic medications only alleviate symptoms by targeting a single molecule, so they can't deal with the complex pathogenesis of AD. The scientific community is actively working to characterise therapeutic agents derived from plants that have shown promise in the literature in treating AD due to their perceived efficacy, safety, and availability. Traditional Chinese medicine includes the use of the plant Centella asiatica for its purported benefits to cognitive performance and memory. Pentacyclic triterpenes are largely responsible for its therapeutic and medicinal effects, which include accelerated enhanced memory. These pentacyclic triterpenoids are asiaticoside and madecassoside as saponins and their aglycones, asiatic acids and madecassic acids. Amongst other triterpenoid Asiatic acid has several therapeutic properties against AD like anti-cholinesterase, neuroprotective and anti-inflammatory. This review focused on the pathophysiology of AD followed by a detailed account on Asiatic acid and the research findings to date related to its mechanism of action on AD, advantage over other two terpenoid, BBB permeability, Pharmacokinetic, molecular docking and different therapeutic activities.